Unresponsive to Cardioversion Pre-excited Irregular Rhythm - Mochamad Yusuf A, MD, PhD; Dara N. Ghassani, M.D; Nupriyanto, MD; Rerdin Julario, M.D (Cardiovascular and Cardiometabolic Journal (CCJ), 2023)
Highlights: 1. Atrial fibrillation in the presence of an accessory pathway may present with confounding electrocardiographic signs. 2. The clinical recognition of WPW may be hindered by the presence of pre-excited AF. - Case Summary: A 46-year-old man without known past medical history was referred to the tertiary hospital emergency department after being found collapsed at home. There are no any complaints of any headache, nausea, chest pain, or paralysis of extremities before losing consciousness. His chest examination to bilateral auscultation was clear. Chest X-ray, routine blood work, and transthoracic echocardiography did not reveal any abnormalities. The initial heart rate before referral was 250-300/min and the ECG shows irregular wide QRS complex tachycardia. The ECG after cardioversions shows sinus rhythm 86 bpm with WPW type A pattern. The patient got intravenous amiodarone and intravenous lidocaine during the transfer. And the ECG on arrival at the emergency department, the heart rate was 50-150 bpm irregularly and the ECG shows atrial fibrillation with a narrow QRS complex. Discussion: Rapid anterograde accessory pathway conduction during atrial fibrillation (AF) can result in sudden cardiac death. During pre-excited AF, delta waves as the key feature of Wolff-Parkinson-White (WPW) syndrome might be obscured. We should keep in mind the diagnosis of pre-excited AF in patients presenting with irregular and wide complex tachycardia.